Plant- and Microbial-Based Organic Disease Management for Grapevines: A Review - Mereke Alimzhanova; Nurkanat Meirbekov; Yerkanat Syrgabek; Rebeca López-Serna; Saltanat Yegemova (Agriculture)
This review compares 32 studies (2000–2024) on plant- and microbial-based organic disease management to control grapevine pests and diseases. A systematic literature search provided 24 studies on microbial agents and 8 on plant treatments. Their effectiveness against key pathogens, including downy mildew, powdery mildew, and gray mold, was compared. Microbial agents such as Candida sake inhibited Botrytis cinerea by up to 80% in the lab and Pseudomonas sp. dramatically reduced grapevine lesion lengths by 32–52% in field conditions, while Bacillus subtilis reduced powdery mildew by 96% in greenhouse conditions and A. pullulans reduced Ochratoxin A infection by 99% in field conditions. In laboratory conditions, C. guilliermondii A42 reduced grape rot to 8–22% and A. cephalosporium B11 reduced it to 16–82%, confirming A42’s greater efficacy. Plant-derived agents and essential oils, including lavender and cinnamon, suppressed 100% of pathogens in vitro, whereas copper coupled with plant-derived agents reduced disease incidence by up to 92% under field conditions. While promising, plant-derived agents are plagued by formulation instability, which affects shelf life and effectiveness, while microbial agents must be kept under stringent storage conditions and can be variable under different vineyard conditions. These limitations identify the requirement for a stronger formulation strategy and large field validations. Organic disease management offers several important benefits, such as environmental safety, biodegradability, compatibility with organic cultivation, and low pesticide dependence. The application of these agents in pest management systems is ecologically balanced, improves soil health, and enables sustainable vineyard management.